Sample average approximation method for a new stochastic personnel assignment problem - Pour, Amir Ghorbani; Naji-Azimi, Zahra; Salari, Majid (Computers & industrial engineering, 2017)
•We introduce a generalization of the standard personnel assignment problem.•The allocated demand to personnel is stochastic.•The problem is applicable in the real world.•We develop a sample average approximation technique to solve the problem.•Results for the real studied problem show the effectiveness of the method. We introduce a practical generalization of the standard personnel assignment problem. In this problem, we have a set of personnel and a set of lost and found centers. Each center receives a stochastic demand. Some constraints, namely, the work skills of different personnel, balancing workload while assigning personnel to the centers and some other practical constraints are taken into account. The objective function is to minimize the assignment cost and the cost occurred by the shortage of personnel in different centers due to the stochastic arrival of the demand over a given time period. We have developed a sample average approximation technique to solve the introduced problem. Computational tests for the studied problem show the effectiveness of the proposed method.